Beyond Terminology: A Qur’an and Hadith Reconstruction of Tarbiyah, Ta’līm, and Ta’dīb - Rasyidin, Rasyidin; Suwanta, Kariawan Adi; Harahap, Radinal Mukhtar (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2025)
This study addresses persistent terminological ambiguity in Islamic education by reconstructing the concepts of tarbiyah, ta’līm, and ta’dīb based on Qur’anic and Hadith sources. While previous studies have examined these terms philosophically or semantically, they often fail to clarify their distinct educational functions and practical implications. This article argues that these concepts represent complementary dimensions of a unified Islamic educational paradigm rather than interchangeable terms. The study employs qualitative text-based religious research using tafsīr tarbawī and ḥadīth maudū‘ī approaches. Qur’anic verses and Prophetic traditions relevant to the three concepts were systematically identified, classified, and analyzed through authoritative classical and contemporary exegesis. Conceptual reconstruction was further guided by Izutsu’s Qur’anic semantic framework to uncover their epistemological, ontological, and axiological orientations. The findings demonstrate that tarbiyah functions as a process-oriented framework emphasizing holistic, gradual human development; ta’līm represents authoritative, ethically grounded knowledge transmission; and ta’dīb serves as the axiological goal of education, centered on the formation of adab. Together, they form an integrated educational paradigm, with pesantren illustrating their organic implementation. As a normative-conceptual study, findings are not empirically generalizable. However, they provide a foundational framework for curriculum design and institutional analysis in Islamic education. This study offers a Qur’an-Hadith-based reconstruction that bridges conceptual debates and educational praxis, contributing a coherent framework for Islamic educational reform.